PENGARUH PERTUMBUHAN EKONOMI DAN UPAH MINIMUM TERHADAP PENYERAPAN TENAGA KERJA DI KOTA DUMAI TAHUN 2010-201 - Refli, Amnur; Yusni, Maulida; Nobel, Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the employment in the city of Dumai which is influenced by economic growth and minimum wages. This study uses multiple linear regression analysis which is assisted by analysis tools, namely the SPSS version 25 program. The independent variables in this study are Economic Growth (X1) and Minimum Wage (X2), while the dependent variable in this study is Labor Absorption (Y). . The results of this study indicate that economic growth has no effect on employment in Dumai City. The minimum wage has a positive effect on employment in Dumai City. And the results of this test are in accordance with the hypothesis that the author has set, which states that the minimum wage has a positive and significant effect on labor absorption.Keywords: Economic Growth, Minimum Wages, Labor Absorption